Dual-Mobility Cup Total Hip Arthroplasty for Displaced Femoral Neck Fractures: A Retrospective Study With a Median Follow-Up of 5 Years - Zhenfa Zhang BM (Geriatric Orthopaedic Surgery & Rehabilitation, 2021)
Introduction: Patient outcomes following modern dual-mobility cup total hip arthroplasty (DM-THA) remains a concern. Few reports have focused on the use of modern DM-THA in the setting of Asian populations for displaced osteoporotic femoral neck fractures (FNFs). This study aimed to investigate the outcomes of Chinese population with displaced osteoporotic FNFs initially treated with modern DM-THA. Materials and Methods: Data from 112 consecutive patients (112 hips) with displaced osteoporotic FNFs initially treated with modern DM-THA during 2011-2018 were retrospectively analyzed. Follow-ups were performed at 3 months, 6 months, 12 months, and then every 1 year after surgery. The primary endpoint was the Harris Hip Score (HHS); the secondary endpoint was the main orthopedic complication rate. Results: The mean HHS improved from 58.62 (±15.79) prior to surgery to 86.13 (±9.92) at the final follow-up. The main complication rate was 14.2% (16/112). Sixteen complications in 10 patients were recorded. Of the 16 complications, there were 2 (1.7%) cases requiring revision DM-THA, 3 (2.6%) cases of loosening, 2 (1.7%) cases of migration, 3 (2.6%) intra-prosthetic dislocation (IPD), 4 (3.5%) cases of tilting, and 2 (1.7%) cases of severe wear. The need for revision was attributed to prosthesis loosening associated with poor bony quality. Conclusion: In patients with displaced osteoporotic FNFs, DM-THA may yield favorable functional outcomes and a low rate of main orthopedic complications, in particular, a low dislocation rate.